External assessment of medical education quality: indicative model development considering paradox of skill - Artyukhov, Artem; Gavurova, Beata; Volk, Iurii; Bilan, Svitlana; Lyeonov, Serhiy; Mudarri, Tawfik (Frontiers in Public Health, 2023)
The current article proposes an approach to the external evaluation of medical education programs' quality based on a combination of indicators, including international rankings, external 'stakeholders' input, and independent agencies' assessments. We modify the success equation with a detailed consideration of the Skill component and its decomposition into internal and external quality assurance elements along with authority. We carried out a bibliometric analysis regarding the problem of medical education quality assessment in the context of achieving sustainable development goals. We described the calculation model of external quality assessment indicators through the algorithms of independent education quality assurance agencies' activity and rating indicators shown in the modified Mauboussin's equation. The model considers the economic component (the consequence of achievement) of Skill, which is expressed in raising funds from external sources to implement educational and scientific activities. The proposed algorithm for assessing the educational program quality can be applied to benchmark educational program components and complete educational programwithin the subject area and the educational institution for different areas. We propose a "financial" model for educational program quality based on the analysis results. The model makes it possible to determine the need for additional focused funding of the educational program based on individual external evaluation criteria analysis of the achievement level. This paper analyzes the accreditation results of more than 110 educational programs for 2020 and 8 months of 2021 within the direction 22 "Medicine" (according to the national classification of fields of knowledge) (state and private Ukrainian medical universities).